2013
DOI: 10.1002/sce.21069
|View full text |Cite
|
Sign up to set email alerts
|

Writing to Learn by Learning to Write During the School Science Laboratory: Helping Middle and High School Students Develop Argumentative Writing Skills as They Learn Core Ideas

Abstract: This study examined how students’ science‐specific argumentative writing skills and understanding of core ideas changed over the course of a school year as they participated in a series of science laboratories designed using the Argument‐Driven Inquiry (ADI) instructional model. The ADI model is a student‐centered and writing‐intensive approach to laboratory instruction. The study was conducted in two middle school and two high school courses offered at a university‐affiliated laboratory school located in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 46 publications
2
91
1
16
Order By: Relevance
“…This learning model can build the logic and critical thinking of students by emphasizing to the role of the argument itself is formed and validate scientific thought [5 and 9]. From the explanation above, researchers have developed a learning model Argument-Driven Inquiry (ADI) into eight stages according to references [8] 1) The task identification, beginning phase where the teacher can ask instructions questions for laboratory experiment that will be conducted; 2) Build data analysis, at this stage the teacher helps students to build a better investigation through some reflective questions. By asking questions to the students that what they would do and why they do so; 3) make temporary arguments, on this steps teachers are asked to provide advice on data that is less complete, less consistent or less accurate.…”
Section: A Argument-driven Inquiry (Adi)mentioning
confidence: 99%
“…This learning model can build the logic and critical thinking of students by emphasizing to the role of the argument itself is formed and validate scientific thought [5 and 9]. From the explanation above, researchers have developed a learning model Argument-Driven Inquiry (ADI) into eight stages according to references [8] 1) The task identification, beginning phase where the teacher can ask instructions questions for laboratory experiment that will be conducted; 2) Build data analysis, at this stage the teacher helps students to build a better investigation through some reflective questions. By asking questions to the students that what they would do and why they do so; 3) make temporary arguments, on this steps teachers are asked to provide advice on data that is less complete, less consistent or less accurate.…”
Section: A Argument-driven Inquiry (Adi)mentioning
confidence: 99%
“…El uso de datos cualitativos y cuantitativos es un imperativo de la argumentación escrita en ciencia escolar (Kelly et al, 2007;Sampson et al, 2011Sampson et al, , 2013 Si bien, con una muestra de 343 participantes, no es posible hacer amplias generalizaciones, sí es coherente señalar que, espontáneamente, los estudiantes hacen uso de vocabulario relacionado con datos cualitativos. Desde una postura didáctica, ello representa una oportunidad de enseñanza para los profesores interesados en promover escenarios de escritura argumentativa, allí los estudiantes podrían enriquecer explícitamente el uso reflexivo de este tipo de datos, toda vez que se trata de un elemento trascendental de la argumentación escrita.…”
Section: Hallazgos En Relación a La Categoría: Datos Cualitativosunclassified
“…Recientemente, Sampson et al (2013) intervinieron en una comunidad de aprendizaje, situada al sureste de Estados Unidos, luego de contar con la participación de 294 estudiantes; estos investigadores resaltan que la argumentación escrita es una necesidad de aprendizaje de las ciencias que puede ser enriquecida siempre y cuando sea un objetivo explícito en los propósitos y las prácticas educativas. De este modo, si la comunidad de investigación en didáctica de las ciencias ha confirmado las bondades de la argumentación escrita, entonces ¿por qué está tan ausente en las prácticas escolares?…”
unclassified
See 1 more Smart Citation
“…Most universities have built in a 'First-year Experience' programme which focuses on the development of academic skills such as the ability to make notes. Globally, studies have shown that the quality of notes that students make is related to the grades that they achieve (Sampson, Enderle, Grooms & Witte, 2013;Trevors, Duffy & Azevedo, 2014). This study focuses on the relationship between the students' note-making practices at school and university.…”
Section: Introductionmentioning
confidence: 99%